Degradação fotocatalítica de corantes têxteis reativos utilizando catalisadores suportados em zeólita - Mendes, Samira da Silva (2013)
Textile production results in high levels of poilution due to the large volume of effluent produced. These industries consume large amounts of water and chemicais in the processes of dyeing and finishing, including textile dyes that represent a major threat to the environment. Due to the difficulty found to degrade these dyes, since they are chemically stable, the advanced oxidation processes (AOPs), in particular heterogeneous photocatalysis, proved to be a promising method for the removal of organie pollutants from textile effluents. This work aims at the application of heterogeneous photocatalysis to treat textile effluent (synthetic dye solution of Reactive Blue 250 (RB250) and Reactive l3lue 222 (RB222), with concentration of 10 and 100 mg.L-1), using artificial UV-Vis radiation, power of 250 W for 5 h. The catalysts used were prepared with 5% and 10% (mim) of ZnO and Nb205 supported on NaA zeolite by wet impregnation and ion exchange. The catalysts were characterized to identify the structural, morphological and textural characteristics. In the degradation tests of the synthetic dye solution, the following parameters were evaluated: type of catalyst and the influence of the support, initial concentration of dye and the molecular structure of the dyes. The efficiency of the photocatalytic process in discoloration was evaluated in terms of reduction of COD and absorbance (UV-VIS spectrophotometry). Among the catalysts studied, 10% ZnO/NaA was the most efficient, reaching 93% of discoloration and 80% reduction of COD, for a 10 mg.L-1 solution of Reactive Blue 250 dye after 5 h of reaction. The photocatalyst with 10% Nb205/NaA reduced the color by 92% and the COD by 75%. The diluted solutions were more easily degraded following the kinetics of pseudo-fírst order, while degradation of concentrated solutions was lower, with apparent zero order kinetics. The solution of dye Reactive Blue 222 subjected to the treatment showed inferior resuits compared with treatment of RB250, which showed a degradation rate around 50% higher than for that RB222. ZnO and Nb205 catalysts in suspension also achieved good results in the degradation of the dye solution. ZnO achieved decolorization for the 98% RB250 solution and 81% for the RB222 solution, whiie the values for were Nb20582 and 79%, respectively. Tests with three pure zeolites showed that the zeolite helps the photochemical process, probably due to its nucleophilic feature that stabilizes the hydroxyl radicais. The use of supported catalysts was efficient with slightly better results than when used catalysts were suspended mass, which enables the application of photocatalytic process commercially.